Sleep problems related to the influence of pain and quality of life in patients with temporomandibular dysfunction. - Piccin, Chaiane Facco; Pozzebon, Daniela; Corrêa, Eliane Castilhos Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Sleep is an inherent condition of life itself, and the physical and mental health is associated with an efficient sleep which in turn contributes to a good quality of life. Objective: To analyze the association between reports of sleep-related problems and the impact of pain on quality of life, and the frequency of reporting nocturnal oral parafunction in patients with dysfunction temporomandibular. Method: 32 subjects with a diagnosis of dysfunction temporomandibular through protocol “Research Diagnostic Criteria for Temporomandibular Disorders”, were evaluated with the analysis of the association of issues related to the influence of pain on quality of life and sleep-related problems and nocturnal oral parafunction. Results: There was a significant positive relation between the quality of sleep (difficulty falling asleep, waking up at dawn and restless or disturbed sleep) and the influence of pain on quality of life of individuals with dysfunction temporomandibular (interference with daily activities, willingness to participate in leisure, social and family activities and the ability to work) on most issues evaluated. As the nocturnal oral parafunction, 90.62% of the subjects complained of squeaks and/or clenching of the teeth during sleep, and 78.13% reported feeling tired or sore jaw upon waking in the morning. Conclusion: It can be concluded that the greater the occurrence of problems related to sleep, the higher the impact of pain on quality of life of patients